The acceptance of sustainable e-commerce by small and medium-sized enterprises: a case of Vietnam - Chu Ba Quyet (Insights into Regional Development)
E-commerce has been adopted by businesses and consumers in Vietnam for consumption activities, profit-seeking, buying and selling goods, conducting business, competing, and expanding markets. Businesses have chosen e-commerce due to its benefits, the trend of applying digital technology, and the ongoing modern business environment. Many studies have identified factors influencing the acceptance of e-commerce, but only some studies have approached sustainable e-commerce. Developing sustainable e-commerce requires businesses to invest more money and technology in business processes, which consumers may only sometimes accept. This article applies the TOE framework to identify factors influencing the acceptance of sustainable e-commerce by measuring the importance coefficient of these factors. The research results reflect changes in the factors affecting the acceptance of sustainable e-commerce. The study also provides recommendations for stakeholders involved in developing sustainable e-commerce.